Comparative Study on the AC Brekadown Voltage of Palm Fatty Acid Ester Insulation Oils Mixed With Iron Oxide Nanoparticles - Mohd Safwan Mohamad; Hidayat Zainuddin; Sharin Ab Ghani; Imran Sutan Chairul (Institute of Advanced Engineering and Science, 2016)
Mineral oils are are derived from petroleum which is a non-renewable and non-sustainable source, and therefore there is a critical need to develop alternative insulation oils for use in transformers. Ester oils offer a number of benefits over mineral oils such as good biodegradability, high cooling stability, good oxidation stability and excellent insulation performance. Nowadays, nanotechnology has become one of the most important research fields in both the academia and industry and it has been shown in previous studies that nanoscale materials are beneficial for transformers. In this regard, the objective of this study is to compare the AC breakdown voltage of palm fatty acid ester (PFAE) oils mixed with iron oxide (Fe3O4) nanoparticles. The PFAE-based nanofluids are prepared using two methods: (1) Method I (weight-based method whereby the concentration of the Fe3O4 nanoparticles is 0.01 g/l) and (2) Method II (volume-fraction method whereby the concentration of the Fe3O4 nanoparticles is 0.01, 0.02 and 0.03%). The AC breakdown voltage test is conducted on the PFAE-based nanofluids in accordance with the ASTM D1816 standard test method. Weibull statistical analysis is carried out to analyse the AC breakdown voltage of fresh PFAE oil and PFAE-based nanofluids. It is found that there is enhancement of the AC breakdown voltage for all PFAE-based nanofluids with the exception of with the exception of one sample prepared using Method II (0.01% Fe3O4 nanoparticles).